PERFORMANCE OF MICROWAVE PRETREATMENT ON ENZYMATIC AND MICROWAVE HYDROLYSIS OF BETUNG BAMBOO (Dendrocalamus asper) - Fatriasari, Widya; Syafii, Wasrin; Wistara, Nyoman; Syamsu, Khaswar; Prasetya, Bambang (Teknologi Indonesia, 2014)
In this present study, we focused on how the changes in the best microwave pretreatment affected the performance of enzymatic and microwave hydrolysis of pretreated bamboo. This solid fraction was subjected to enzymatic hydrolysis following NRE L protocol and microwave acid-hydrolysis with/without presence of activated carbon (0.5 g/g) at 1% and 5% of sulfuric acid concentration for 512.5 m at 330 watt. Short duration microwave-acid hydrolysis of microwave pretreated bamboo showed better reducing sugar yield than that of enzymatic one. Microwave heating for 12.5 inm at 330 W hydrolyzed with 1% acid using microwave irradiation demonstrated a high reducing sugar yield (25.81% of dry biomass or 27.12% of dry substrate). In this treatment, 37.92% of hollocellulose can be converted into reducing sugar or equivalent to 36.12% of maximum potential sugar released. This yield was increased 6.09 times compared to the highest reducing sugar yield coming from enzymatic hydrolysis using 20 FPU/g of cellulase enzymes. Reducing sugar yield obtained with 5% microwave acid hydrolysis of microwave pretreatment for 5 m at 770 W was equal to the result of hydrolysis for 12.5 m at 330 W. Unfortunately, the activated carbon as solid catalyst in microwave hydrolysis could only reduce brown compound without reducing sugar yield improvement.